Holistic Management in Adolescent Patients with Atopic Dermatitis Through Family Medicine Approach: A Case Report - Anita, Anita; Moningkey, Shirley; Handoko, Marshell (Faculty of Medicine, Public Health, and Nursing, 2024)
Atopic Dermatitis (AD) is a chronic, recurrent skin inflammation accompanied by itching and occurring in specific areas of the body. AD is often associated with other atopic diseases such as allergic rhinitis and bronchial asthma. It can affect individuals of all ages but is most common in infants and children. AD that appears in adolescents and adults is also increasingly recognized. This case report aims to explore the role of family physicians in the holistic and comprehensive management of AD in adolescents through a family medicine approach to prevent relapses and reduce the severity of AD. Data were obtained through auto-anamnesis, physical examination, and home visits. LAK, a 21-year-old final-year student, reported a red rash on her upper right arm for the past month, which she found very bothersome. Internal factors aggravating her symptoms included her mother's allergic rhinitis, the patient never using skin moisturizers, and not cleaning her body immediately after sweating. External factors included having to walk to campus through busy, hot, and dusty roads and the stress from her final-year thesis. Diagnosis and management were carried out holistically through patient-centered, family-focused, and community-oriented. The family medicine approach emphasizes prevention, patient education, and long-term management to reduce the severity of AD. Through a family medicine approach, changes in behavior, particularly in prevention, will occur, allowing AD to be managed and preventing relapses